2001
DOI: 10.1177/0734242x0101900306
|View full text |Cite
|
Sign up to set email alerts
|

Composition of leachate from old landfills in Denmark

Abstract: The Danish counties have performed numerous investigations of old landfills. These investigations have been presented in several reports, but no comprehensive summary of the findings has been carried out. The objective of this study was to evaluate the typical composition of leachates from old smaller landfills by a comprehensive review of the investigations carried out by the counties. In total 106 landfills were selected by criteria avoiding dilution effects. A database was constructed using a standard progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 6 publications
5
51
0
3
Order By: Relevance
“…However, recent studies have shown that the quality of leachate analysis for XOCs is seriously jeopardized only if very poor sampling protocols are used (see review by Parker, 1994 (Assmuth and Strandberg, 1993;Kjeldsen and Christophersen, 2001). In general, landfill leachates may contain very high concentrations of dissolved organic matter and inorganic macrocomponents.…”
Section: A How Representative Are Leachate Samples?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have shown that the quality of leachate analysis for XOCs is seriously jeopardized only if very poor sampling protocols are used (see review by Parker, 1994 (Assmuth and Strandberg, 1993;Kjeldsen and Christophersen, 2001). In general, landfill leachates may contain very high concentrations of dissolved organic matter and inorganic macrocomponents.…”
Section: A How Representative Are Leachate Samples?mentioning
confidence: 99%
“…This has been shown by several studies in which researchers have reported metals concentrations from full-scale landfills, test cells, and laboratory studies. The ultimate conclusion of all of these studies is that heavy metals in landfill leachate at present are not at major concern Robinson, 1995;Reinhart and Grosh, 1999;Revans et al, 1999;Kjeldsen and Christophersen, 2001;Christensen et al, 1994). Table 5 gives more details of observed heavy metal concentrations.…”
Section: E Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est le cas du phosphore dont la concentration est généralement faible dans les lixiviats matures. Sur 106 lixiviats matures étudiés, KJELDSEN et CHRISTOPHERSEN (2001) ont rapporté une valeur moyenne de Pt = 2,7 mg•L -1…”
Section: Tendances Futures Et Perspec-tives Des Procédés éLectro-chimunclassified
“…The reported full composition of leachates of different municipal solid waste landfills all over the world were presented by e.g. Ehrig (1989); Fatta et al (1998), Kjeldsen & Christoffersen (2001), Kylefors (2003), Kulikowska & Klimiuk (2008); Tatsi & Zouboulis (2002) and Ziyang et al (2009). Migration of leachates generated inside the waste body of municipal landfill to soil and groundwater is prevented by bottom liners of different construction based on porous materials of low permeability.…”
Section: Influence Of Leachates On Water Permeabilitymentioning
confidence: 99%